Age of alcohol use initiation and psychiatric symptoms among young adult trauma survivors. (January 2019) - Berenz, Erin C.; McNett, Sage; Rappaport, Lance M.; Vujanovic, Anka A.; Viana, Andres G.; Dick, Danielle; Amstadter, Ananda B.
Abstract: Alcohol use disorder (AUD) evidences high rates of comorbidity with a range of psychiatric disorders, particularly within high-risk populations, such as individuals exposed to physical or sexual violence. Increasing efforts are focused on understanding the role of early alcohol use (e.g., during adolescence) on emotional and psychiatric functioning over time, as well as sex differences in these associations. The aim of the current study was to evaluate patterns of association between age of initiation of regular alcohol use and posttraumatic stress disorder (PTSD), anxiety, and depressive symptoms as a function of sex. Participants were 269 college students with a history of interpersonal trauma and alcohol use who completed a battery of questionnaires regarding alcohol use and emotional health. Neither bivariate correlations nor results from structural equation models covarying for key factors showed a relationship between age of alcohol use initiation and current psychiatric symptoms among men ( n = 63). Results of a structural equation model supported an association between earlier age of alcohol use initiation and greater levels of current PTSD (β = −0.14), anxiety (β = −0.15), and depression symptoms (β = −0.16) in the female sub-sample ( n = 202), after controlling for covariates, as well as intercorrelations among criterion variables. Statistical support for sex as a moderator of these associations was not detected. The current study provides preliminary evidence for potential sex differences in the role of early alcohol use in the development of psychiatric symptoms and highlights the need for systematic longitudinal research. Highlights: Earlier age of initiation of alcohol use associated with greater psychiatric symptoms Age of initiation of alcohol use associated with symptoms for women but not men Association between age of initiation and symptoms not accounted for by trauma load